Adaptive Physical Activity for Stroke: An Early-Stage Randomized Controlled Trial in the United States. (August 2019) - Stuart, Mary; Dromerick, Alexander W.; Macko, Richard; Benvenuti, Francesco; Beamer, Brock; Sorkin, John; Chard, Sarah; Weinrich, Michael
Background . As stroke survival improves, there is an increasing need for effective, low-cost programs to reduce deconditioning and improve mobility. Objective . To conduct a phase II trial examining whether the community-based Italian Adaptive Physical Activity exercise program for stroke survivors (APA-Stroke) is safe, effective, and feasible in the United States. Methods . In this single-blind, randomized controlled trial, 76 stroke survivors with mild to moderate hemiparesis >6 months were randomized to either APA-Stroke (N = 43) or Sittercise (N = 33). APA-Stroke is a progressive group exercise regimen tailored to hemiparesis that includes walking, strength, and balance training. Sittercise, a seated, nonprogressive aerobic upper body general exercise program, served as the control. Both interventions were 1 hour, 3 times weekly, in 5 community locations, supervised by exercise instructors. Results . A total of 76 participants aged 63.9 ± 1.2 years, mean months poststroke 61.8 ± 9.3, were included. There were no serious adverse events; completion rates were 58% for APA-Stroke, 70% for Sittercise. APA-Stroke participants improved significantly in walking speed. Sample size was inadequate to demonstrate significant between-group differences. Financial and logistical feasibility of the program has been demonstrated. Ongoing APA classes have been offered to >200 participants in county Senior Centers since study completion. Conclusion . APA-Stroke shows great promise as a low-cost, feasible intervention. It significantly increased walking speed. Safety and feasibility in the US context are demonstrated. A pivotal clinical trial is required to determine whether APA-Stroke should be considered standard of care.